2016
DOI: 10.1089/cap.2015.0055
|View full text |Cite
|
Sign up to set email alerts
|

The Case for Telemental Health for Improving the Accessibility and Quality of Children's Mental Health Services

Abstract: Authors in this special edition are experienced TMH innovators and providers, and offer expert perspectives on the current and evolving status of TMH practice in child and adolescent mental health. The articles in this collection draw on leading TMH examples, using a range of interventions implemented across diverse TMH settings, to systematically address the critical technical, ethical, regulatory, clinical, and service delivery aspects of TMH care. These articles strategically outline the key considerations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“…Telehealth technology is increasingly used as an element of delivery of MH care, and thus, practices may have the technological tools and knowledge in place to use this intervention. 59 There are some key limitations to our findings. First, the referral system was created to address the specific needs of the community partners and, thus, may need adaptation to be generalizable to other locations or settings.…”
Section: Discussionmentioning
confidence: 83%
“…Telehealth technology is increasingly used as an element of delivery of MH care, and thus, practices may have the technological tools and knowledge in place to use this intervention. 59 There are some key limitations to our findings. First, the referral system was created to address the specific needs of the community partners and, thus, may need adaptation to be generalizable to other locations or settings.…”
Section: Discussionmentioning
confidence: 83%
“…The literature review of this study adopted the convergence and business model innovation concept to provide a concise and up-to-date review that accounts for the influence of technology and social phenomena [16]. Current literature on CH implementation is emergent and has illustrated how technology enables a more connected healthcare system; specifically, the improvement of healthcare accessibility, cost-effectiveness, and quality of life [17][18][19][20]. Nevertheless, there are many unexplored areas relating to business sustainability in terms of quality, cost, increased technology, and future development in CH [21].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The purpose of this study was to learn about the associations among HIV/AIDS, pain and heavy drinking among patients in HIV-care in order to tailor a videoconferencing intervention for chronic pain and heavy drinking. We chose videoconferencing as our platform because studies across a number of disorders have shown its advantages for improving adherence particularly among populations that face significant barriers to treatment, such as low-income populations [2123]. Videoconferencing has a distinct advantage over many other forms of telehealth in that it provides the interventionist with real time information about how patients are able to utilize skills and provides the capacity to provide synchronous training and feedback.…”
Section: Introductionmentioning
confidence: 99%